The Effect of Steaming Time on the Textural Characteristics of Two Sweet Potatoes with Different Flesh Colors - Joko Susilo Utomo; Erliana Ginting (Balai Penelitian Tanaman Aneka Kacang dan Umbi, 2021)
Sweet potatoes have varied physical characteristics based on their flesh colors. Two selected sweet potato (SP) with white (WF) and yellow-fleshed (YF) colors were collected from local market and analyzed their textural characteristics using a Uniaxial compression and Texture Profile Analysis (TPA) test. The study was conducted in the Food Processing Technology Laboratory, Faculty of Food Science Technology, University of Putra Malaysia. All textural attributes were collected from the samples treated with steaming for 5, 10, 15 and 20 min. The moisture content of the samples were determined before and after steaming. The results showed that the moisture content of WF was lower than YF both before and after steaming, which could be declared as a typical moisture content for each flesh color. This resulted in a greater peak deformation or firmness of the fresh tuber found in WF relative to YF. Steaming SP for 5 min exhibited the “raw” properties tissue, whereas steaming for more than 10 min would generate the “cooked” tissue that significantly affected the textural characteristics. The hardness level decreased considerably along with the time of steaming and was similar for both flesh colors after 15-min steaming. The WF was less adhesive and less elastic; however, it had less chewiness than that of YF. This suggests that the use of WF as a raw material for mashed products would have advantages, such as easiness to mash, less tendency to stick with the cooking tools, and less elastic.